THE EFFECTIVENESS OF USING BOARD RACE GAME IN INCREASING STUDENTS’ VOCABULARY MASTERY - Tumboimbela, Teresa; Mogea, Tini; Kumayas, Tirza (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
A vocabulary is a collection of terms from a language that, when utilized, provides meaning. Students should value their vocabulary because it is necessary for all actions in order to receive and produce language. This implies that pupils will find it simpler to generate numerous phrases both vocally and in writing as they gain vocabulary mastery. There are many types of teaching media to teach vocabulary, one of which is using board race games. This study sought to ascertain how Board Race might be used to enhance students' mastery of vocabulary. This study was conducted on 20 students of class VIII in SMP N 4 Tombatu. Data for this study were gathered using a pre-experimental design and quantitative methodology utilizing pre- and post-test results. The average pre-test score was 58.50, while the average post-test score was 82.50. Based on these results, it can be concluded that board race has a significant impact on student achievement to improve vocabulary mastery of grade VIII students at SMP Negeri 4 Tombatu. It is advised that educators utilize board games with races as a way to introduce language to their students.